Pengembangan LKS Praktikum Berbasis KPS (Keterampilan Proses Sains) Untuk Meningkatkan Penguasaan Konsep Dan Sikap Ilmiah Siswa - Hindriana, Anna Fitri; Nur, Sofyan Hasanuddin (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2020)
The purpose of this study is to (1) Determine the validity of KPS-Based Student Worksheet practicum based on the results of the development (2) To describe the functioning of the results of the development of KPS-based Student Worksheet practicum on food substances test, (3) Analyze the effectiveness of KPS-based Student Worksheet practicum on the improvement of concept mastery on the Food Substance Test practicum, (4) Analyzing the effectiveness of KPS-based Student Worksheet practicum on improving students' scientific attitudes on the Food Substance Test practicum. The research method uses a mixed approach (mix methods). Exploratory research design. The sample used as many as 36 students. Data collection techniques using multiple choice test questions, questionnaires, observation sheets, and documentation. Data analysis techniques used descriptive analysis and average difference test, and the gain index. Based on the results of the study it was concluded that: (1) The assessment of the KPS-based Student Worksheets practicum developed was valid based on validator 1 and 2 assessments from didactic, linguistic, construction and engineering aspects. (2) Based on teacher and student assessment responses the functioning of the KPS-based Student Worksheets practicum that is developed is included in both categories in accordance with aspects of the assessment of the appropriateness of content, linguistic, presentation and graphic. (3) The development of KPS-based Student Worksheet practicum is very effective to improve students concept mastery because students are guided in making observations, interpreting observations, classifying and predicting. Thus the first research hypothesis was proven. (4) The development of KPS-based Student Worksheet practicum is very effective to improve students scientific attitudes, especially the attitude of curiosity, honest attitude, conscientious attitude and attitude of responsibility.